Starter packs [ a strategy to fight hunger in developing countries? : lessons from the Malawi experience 1998-2003 - Levy, Sarah , 1964- (CABI, 2005)
This book is about the Starter Pack/Targeted Inputs Programme, which was implemented in Malawi from the 1998-99 agricultural season to the 2003/04 season. The original idea of Starter Pack was to give a bag of free agricultural inputs (fertilizer and sed) to every smallholder farmer in Malawi. Although the programme did not work as originally intended, it was successful in achieving national food security. The scaling down of the programme was a major contributor to the food crisis that hit Malawi (and other countries in southern Africa) at the beginning of 2002. The book (with accompanying CD) assesses the case of the Starter Pack programme in Malawi, and whether it can be replicated elsewhere. Part 1 (chapters 1-4) tells the story of how the programme was designed and implemented. Part 2 (chapters 5-7) outlines the evaluation methods used to produce the policy lessons presented in part 3 (chapters 8-15). Part 4 (chapters 16-19) comprises four essays by external academics and consultants, which assess the programme from different perspectives. The book has a subject index.